Green Chemistry, Characterization and Study of Medical Application Silver/ Polymer Nanocomposite - Khalidah Khalaf Jabbar (Journal of Global Pharma Technology, 2019)
Over the last few years, the green consistency over nanoparticles (NPs) the usage of drive into extracts has emerged as a hopeful methodology because of the fabrication of metal NPs (especially silver, copper, and riches NPs), so kind of it entails an easy, fast, low-cost, then environmentally pleasant bioprocess. The consistency atop nanoparticles through the use of the biochemical rejoinder regarding propulsion dust reply since page banish as regards but facile, quick & eco-friendly microwave assisted adjustment of doublet polymers polymethyl methacrylate & poly butyl methacrylate and joining nanocomposites Ag/Polymethyl methacrylate (Ag/PMMA) then Ag/ Poly butyl methacrylate (Ag/PBMA). The synthesized nanoparticles had been characterized through FT-IR, UV-visible, X-Ray Diffraction (XRD) afterward Transmission Electron Microscopic (TEM) studies. Nanocomposites, Scanning Electron Microscopy (SEM) and TG/DTA.XRD studies but TEM pictures evolved average particle quantity concerning synthesized nanoparticles 20 nm. Thermal lookup rose that standard hot regarding Ag/PMMA then Ag/PBMA nanocomposites reduced as it should be among pursuance with city related to Ag nanoparticles of the polymer matrix.Keywords: Green synthesis, Metal nanoparticles, Metal/ Polymer Nanocomposite, Medical Application